Instructional Content and Quality of Business Studies Textbook in Secondary School in Kenya - Getahun, Bekele Sarah; Amollo, Odundo Paul; Kamau, Mwangi John; Lilian, Ganira Khavugwi (International Journal of Educational Technology and Learning, 2022)
Adequately planned business studies textbook promotes effective independent learning among learners yielding achievement of learning outcome for sustained academic results. Business textbook represents potentially implemented curriculum as its vehicle through which intended content of curriculum is availed to learner encouraging actualization of learning objectives. However, instructional information that does not facilitate realization of specific objectives may limit knowledge construction degrading learner’s mean score in business studies. The study adopted exploratory research design through quantitative and qualitative approach to data collection and analysis. Counts, percentages, means, standard deviations, Chi square tests and content analysis were used for data analysis. Cross tabulation results indicated that instructional content significantly influence quality of textbook implying that appropriate instructional information supports achievement of learning for prolonged learning experience. Further analysis showed that presentation style, learner cognition and visual representation influence quality of instruction content encouraging learning. Therefore, it is recommended that educational material incorporated in business textbook be relevant to learner cognition to accelerate learning.